2000
DOI: 10.1007/bf02462617
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium nitroprusside on mediator release and the functional properties of postsynaptic membranes in the neuromuscular synapse

Abstract: Experiments on neuromuscular preparations of frog skin- thoracic muscle and sartorius muscle, using extracellular recording and two-electrode clamping of the muscle fiber membrane potential, were used to study the effects of the nitric oxide donor sodium nitroprusside on endplate currents. At a concentration of 100 microM, sodium nitroprusside sharply decreased the amplitude and quantum composition of the endplate currents, and also decreased the miniature endplate current frequency. The amplitude-time charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…NO synthase is present in frog perisynaptic Schwann cells (Descarries et al 1998) and NO has been suggested as a diffusible messenger mediating the action of adenosine at the neuromuscular junction (Rochon et al 2001;Auld & Robitaille, 2003). In our experiments SNP or SNAP, two NO donors, reduced EPCs in accordance with the previous observations (Lindgren & Laird, 1994;Zefirov et al 2000). In keeping with data obtained previously (Rochon et al 2001;Auld & Robitaille, 2003) the inhibitory effect of adenosine on EPCs was reduced in the presence of a high dose of SNAP.…”
Section: Action Of Anti-and Pro-oxidants Suggested Involvement Of Rossupporting
confidence: 93%
“…NO synthase is present in frog perisynaptic Schwann cells (Descarries et al 1998) and NO has been suggested as a diffusible messenger mediating the action of adenosine at the neuromuscular junction (Rochon et al 2001;Auld & Robitaille, 2003). In our experiments SNP or SNAP, two NO donors, reduced EPCs in accordance with the previous observations (Lindgren & Laird, 1994;Zefirov et al 2000). In keeping with data obtained previously (Rochon et al 2001;Auld & Robitaille, 2003) the inhibitory effect of adenosine on EPCs was reduced in the presence of a high dose of SNAP.…”
Section: Action Of Anti-and Pro-oxidants Suggested Involvement Of Rossupporting
confidence: 93%
“…It is well known [17][18][19] that NO participates in the development, maturation and aging of brain, forros learning and memory processes. At the moment it is considered that NO plays the role of a signal molecule in different parts of the nervous system influencing the function of synaptic formations.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with sodium nitroprusside (SN) as the NO donor showed that exogenous NO decreases the amplitudes of endplate potentials (EPP) evoked by motor nerve stimulation and frequency of miniature endplate potentials (MEPP) in frog neuromuscular synapse, without affecting their amplitude and dependence on membrane potential. These data suggest that exogenous NO has a presynaptic effect that moderates quantal secretion of the transmitter from motor terminals without modifying the function of chemosensitive ionic channels in the postsynaptic membrane [4,10]. However, the mechanisms of the presynaptic effects of NO are poorly understood.…”
mentioning
confidence: 97%
“…Blockade of action potentials and muscle contraction, as well as attenuation of endplate ionic currents were performed by adding of tubocurarine (0.02 mM) into the perfusion solution. The evoked responses of nerve terminals, EPP, and MEPP were recorded with extracellular glass microelectrodes (tip diameter 2-5 la) filled with 1 M NaCl [1][2][3][4]. Quantal composition of the endplate currents was calculated by falling (probability) analysis [9]: m--In n/no, where n is the number of stimuli and n o is the number of realizations.…”
mentioning
confidence: 99%